Are 'New' Donors Different? Comparing the Allocation of Bilateral Aid between Non-DAC and DAC Donor Countries - Axel Dreher; Peter Nunnenkamp; Rainer Thiele (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2010)
Major DAC donors are widely criticized for weak targeting of aid, selfish aid motives and insufficient coordination. The emergence of an increasing number of new donors may further complicate the coordination of international aid efforts. On the other hand, new donors (many of which were aid recipients until recently) may have competitive advantages in allocating aid according to need and merit. Project-level data on aid by new donors, as collected by the PLAID initiative, allow for empirical analyses comparing the allocation behavior of new versus old donors. We employ Probit and Tobit models and test for significant differences in the distribution of aid by new and old donors across recipient countries. We find that new donors (i) focus on closer neighbors, (ii) care less for recipient need, (iii) exhibit a weaker bias towards badly governed countries, (iv) respond to disasters, but with fewer resources than old donors, and (v) do not pursue commercial self interest.
Keywords: F35; 330; aid allocation; new donors; donor motives; Probit; Tobit